EFEKTIVITAS BISINDO (BAHASA ISYARAT INDONESIA) PROGRAM SIARAN REDAKSI SORE TRANS7 PADA BALI DEAF COMMUNITY - Azmir, Miranda; Purawan, Ni Luh Ramaswati; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2019)
ABSTRACT To fulfill the need of information for the hearing im-paired, since 2017 news program in television translation in sign language has been provided. Focus of this study is measure the effectiveness of Redaksi Sore TRANS7 BISINDO on Bali Deaf Community, a community who does socializing BISINDO. This study used Direct Rating Method as indicator and Uses and Effect theory. This study did the instrument testing using validity and reliable test and statistics descriptive analysis. The result is, average score of the effectiveness of Redaksi Sore TRANS7 BISINDO is 69,98 and shows that there are five indicator on DRM that influence the effectiveness, such as attention, readthroughness, cognitive response, affective response, and behavioral response. The primary principlethis theory is whether the users (Bali Deaf Community) receive an effect after using mass media (Redaksi Sore TRANS7 with sign language translator). Keywords: Bali Deaf Community, BISINDO (Indonesia Sign language), Mass Media